Leukemia - Hochhaus, Andreas; Gale, Robert Peter; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Springer Nature.)
Leukemia covers all aspects of the research and treatment of leukemia and allied diseases. Studies of normal hemopoiesis are covered because of their comparative relevance. Topics of interest include oncogenes, growth factors, stem cells, leukemia genomics, cell cycle, signal transduction, molecular targets for therapy and more.
Keywords: Cancer research; Medicine; Critical care medicine; Internal medicine; Hematology; Oncology; Medicine/Public Health, general; Internal Medicine; Intensive / Critical Care Medicine; Cancer Research; Oncology; Hematology